Optimizing crop geometry for processing-grade tuber yield, quality and economics of potato in Grey Terrace Soil. Issue 11 (1st November 2016) - Alam, Shamshul; Islam, Nazrul; Hossain, Jahangir; Islam, Monirul; Bhuiyan, Shahidur Rashid; Hossain, Ismail
ABSTRACT: Crop geometry has great influence on economically important characteristics such as total yield, processing-grade yield, tuber size distribution and tuber quality in Grey Terrace Soil. An experiment was conducted to develop a suitable crop geometry for the production of higher processing-grade yield and quality of potato tubers. The treatment consisted of three levels of inter-row spacing (60, 67.5 and 75 cm) and four levels of intra-row spacing (20, 25, 30 and 35 cm). Crop geometry significantly influenced growth, yield contributing characters, tuber size distribution and yield of potato. The highest chips, French fry grade tubers and total potato tuber yield were found in 67.5 cm × 25 cm crop geometry without affecting processing quality but all were in the highly acceptable range. Intra-row spacing of 25 cm produced the maximum processing quality tubers, closely followed by 30 cm. The highest gross and net returns with a benefit–cost ratio of 1.75 were recorded in 67.5 cm × 25 cm crop geometry. Therefore, the 67.5 cm × 25 cm crop geometry can be recommended for higher potato tuber yield and processing-grade tubers as well as higher economic return.